The Effect of Return on Equity, Loan to Deposit Ratio, Non-Performing Loan, and Capital Adequacy Ratio on the Price of Banking Stocks Listed on the Indonesia Stock Exchange in the Period 2011-2020 - Sumantri, Muhammad Bayu Aji (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to study the effect of Return on Equity, Loan to Deposit Ratio, Non-Performing Loan and Capital Adequacy Ratio on banking stock prices listed on the Indonesia Stock Exchange during the period 2011-2020. This study uses banking companies listed on the Indonesia Stock Exchange which always report their financial statements every year and their shares are always traded on the stock exchange during the study period. The research method used is descriptive analysis using multiple linear regression. From this study it was found that Return on Equity, Loan to Deposit Ratio and Capital Adequacy Ratio have a significant influence on banking stock prices. Meanwhile, only the Non-Performing Loan variable has no significant effect on stock prices.